Short-term spider community monitoring after cattle removal in grazed grassland - Silva,Guilherme O. da (2017)
ABSTRACT. At the Pampa Biome, grazing, like others disturbances, affects fauna and flora, creating heterogeneity in the environment. Little is known about how the diversity and richness of arthropods change during this impact. To improve the knowledge of how spider diversity is affected by grazing, experiments were realized at Pampa. The hypothesis is that abundance of spider will be different when comparing grazed and ungrazed areas. A paired block, with two areas of one hectare each, was established in three areas in the Environmental Protection Area of Ibirapuitã (APA Ibirapuitã), state of Rio Grande do Sul, Brazil. One of these hectares was closed with fences, excluding the catle grazing, in August of 2012. Samplings were realized in November of 2011, 2012 and 2013 using Pitfall traps filled with formol 4% and disposed in an “X” format in each area. For statistical analyses, T test, ANOSIM, ANOVA and Rarefaction were performed. A total of 1,315 spiders were captured, comprising 77 species or morphospecies belonging to 20 families. The family most abundant was Lycosidae followed by Hahniidae, Linyphiidae and Theridiidae. Linyphiidae was the richest family with 14 species or morphospecies identified. All spiders, adults and juveniles, only adults in species and morphospecies, and most abundant species were used as models for statistics. These models revealed no significant difference between grazed and ungrazed areas after three and 15 months of cattle exclusion.